CATARACT AND ITS IMPACT ON VISION: MEDICAL, SOCIAL ASPECTS, AND TREATMENT METHODS (International journal of artificial intelligence, 2025)
This article analyzes the negative effects of cataracts on vision, its medical and social consequences, and existing treatment methods. It scientifically examines the impact of cataracts on patients’ quality of life and social activity. Cataract is considered the most common cause of blindness worldwide, mainly affecting older people. The article discusses the causes of the disease, its clinical features, diagnostic methods, and the most effective surgical treatment options. In addition, the influence of cataracts on patients’ daily lives and the healthcare system is highlighted. The paper emphasizes the importance of preventive measures and the need to raise public awareness in combating cataracts. Cataract is a disease in which the transparency of the eye lens is lost, leading to decreased vision. It can affect one or both eyes. Treatment usually involves surgical replacement of the damaged lens with an artificial one.